2019
DOI: 10.1186/s13018-019-1407-3
|View full text |Cite
|
Sign up to set email alerts
|

Modern instant messaging platform for postoperative follow-up of patients after total joint arthroplasty may reduce re-admission rate

Abstract: Background: Follow-up after artificial joint replacement greatly helps achieve surgical outcomes. Mobile internet technology and mobile terminal equipment may increase the effectiveness of artificial joint replacement. However, only a few studies have evaluated the effectiveness of this technology. We aimed to analyze the reasons and outcomes of patients who used the instant messaging platform after undergoing artificial joint replacement. Methods: Among the 548 cases of arthroplasty (250 hips, 298 knees) perf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(21 citation statements)
references
References 23 publications
0
21
0
Order By: Relevance
“…Several studies describe patient satisfaction with telehealth programs [ 68 , 69 , 70 , 71 , 72 , 73 ]. Buvik et al [ 74 ] found, in a randomized controlled trial, that 86% of patients having remote consultations preferred a video-assisted consultation for the next visit.…”
Section: Resultsmentioning
confidence: 99%
“…Several studies describe patient satisfaction with telehealth programs [ 68 , 69 , 70 , 71 , 72 , 73 ]. Buvik et al [ 74 ] found, in a randomized controlled trial, that 86% of patients having remote consultations preferred a video-assisted consultation for the next visit.…”
Section: Resultsmentioning
confidence: 99%
“…A systematic review has been conducted (Bahadori et al, 2020). The remaining nine articles were observational studies categorized as prospective comparative studies, before-and-after studies, retrospective studies, and case studies (Berg et al, 2018; Dehorney & Ashcraft, 2018; Gabor et al, 2020; Glans et al, 2020; Gruskay et al, 2019; Harris et al, 2021; Lyman et al, 2020; Mascioli et al, 2021; Oosterholt et al, 2017; Zheng et al, 2019).…”
Section: Results and Discussion Characterization Of The Body Of Liter...mentioning
confidence: 99%
“…Researchers have established that using a fast-track, streamlined educational protocol or a recovery instant messaging, educational application can reduce the rate of readmission in patients undergoing TJR (Bahadori et al, 2020; Berg et al, 2018; Campbell et al, 2019; Gabor et al, 2020; Hussain et al, 2017; Lyman et al, 2020; Stauber et al, 2020; Timmers et al, 2019; Zheng et al, 2019). A common theme among all articles was that same-day outpatient TJR patients who received adequate and streamlined perioperative education had fewer readmissions in the 30-day postoperative period.…”
Section: Results and Discussion Characterization Of The Body Of Liter...mentioning
confidence: 99%
“…There is also evidence that text message reminders can be used for pre-operative optimization for improved outcomes [12]. A number of programs involved in the post-discharge setting have been developed including postpartum care, post-operative care, and treatment of chronic heart failure and hypertension [13][14][15][16]. These programs also support the notion that text messaging with patients can serve to educate, remind about key components of care, and provide positive feedback.…”
Section: Discussionmentioning
confidence: 99%